Long‐term remission of severe livedoid vasculopathy treated with a short course of intravenous immunoglobulin. Issue 6 (8th September 2021) - Takahagi, Shunsuke; Tanaka, Maiko; Morioke, Satoshi; Suehiro, Masataka; Tanaka, Akio; Hide, Michihiro
Abstract : We present a case of acute flare of severe livedoid vasculitis (LV) which had been refractory to a combination of immunosuppressive and anti‐thrombotic agents, but remitted for 7 years after only two cycles of intravenous immunoglobulin (IVIV). This suggests that IVIG may exert unique immunological and/or anti‐thrombotic actions different from other agents, and that only short‐term or on‐demand use of IVIG for acute flare of LV may dampen down disease activity and induce a prolonged remission of LV.